University History in the Low Countries - Frijhoff, Willem (CIAN-Revista de Historia de las Universidades, 2017)
The University history of the Low Countries is largely tributary of the different fate of the two halves of that region. In the South (present-day Belgium), in fact a unitary state from the 16th century onwards, the University of Louvain, initially founded for the whole Low Countries, was long the only institution of higher education. It was temporarily joined by that of Douai (later incorporated into France). In the North (the present-day Netherlands), universities and other institutions of higher education were only founded from the independence in the late 16th century onwards, but then in huge numbers, due to the confederal character of the Dutch Republic. In the revolutionary and Napoleonic era, the whole university landscape was thoroughly altered, and most of the institutions in the North suppressed. After 1815, new universities were founded on the same footing in both countries, then again temporarily united. Although the Netherlands and Belgium went their own way ever since their separation in 1830, both countries show a similar institutional evolution, in  spite of the linguistic problems in the South. This is reflected in the cooperation between scholars on university history of the whole Low Countries region. In this article, I first sketch briefly the political evolution of the Low Countries and that of the university landscape and its institutional provisions, compulsory for a good comprehension of the university historiography. After a survey of the process of institutionalisation of university history in the European context ever since the 1980s, the (bi-)national associations and the renewal of the focus on the social dimension of university history and the history of science are briefly discussed. Throughout the article, the most important studies and memorial volumes of the last decades are quoted.
Keywords: historiography; Low Countries; universities; colleges; Latin schools